The Role of the Lateral Hypothalamus in Violent Intraspecific Aggression—The Glucocorticoid Deficit Hypothesis - Haller, József (Frontiers in Systems Neuroscience, 2018)
This review argues for a central role of the lateral hypothalamus in those deviant forms of aggression, which result from chronic glucocorticoid deficiency. Currently, this nucleus is considered a key region of the mechanisms that control predatory aggression. However, recent findings demonstrate that it is strongly activated by aggression in subjects with a chronically downregulated HPA-axis; moreover, this activation is causally involved in the emergence of violent aggression. The review has two parts. In the first part, we review human findings demonstrating that under certain conditions, strong stressors downregulate the HPA-axis on the long run, and that the resulting glucocorticoid deficiency is associated with violent aggression including aggressive delinquency and aggression-related psychopathologies. The second part addresses neural mechanisms in animals. We show that the experimental downregulation of HPA-axis function elicits violent aggression in rodents, and the activation of the brain circuitry that originally subserves predatory aggression accompanies this change. The lateral hypothalamus is not only an integrant part of this circuitry, but can elicit deviant and violent forms of aggression. Finally, we formulate a hypothesis on the pathway that connects unfavorable social conditions to violent aggression via the neural circuitry that includes the lateral hypothalamus.